Health Behaviors and Fasting Blood Sugar Levels of Muslims with Type 2 Diabetes - Mansakul, Tanyawan; Chansawang, Wannee; Petchruschatachart, Usanee (Journal of Health Science of Thailand, 2018)
The purpose of this descriptive research was to describe health behaviors and fasting blood sugar levels of Muslims with type 2 diabetes mellitus during normal and Ramadan period. The study samples, randomly selected, consisted of 118 Muslim patients with type 2 diabetes mellitus from Out - patient Department of Yingo His Majesty the King’ s 80th Birthday Hospital. Two stages of data collection were conducted. The 1st stage was done in October 2008 using a set of questionnaire on health behavior during Ramadon period (r = 0.80), and the 2nd stage was completed between December 2008 and February 2009 using a set of questionnaire on health behavior during normal period (r = 0.83). The data collected was analyzed using frequency, percentage, mean and standard deviation. The results revealed that in the normal period the total mean score of health behavior (x̅ 1.70, 0.43), and those of individual four dimensions (drug management: x̅ 1.95, 0.20; diet management: x̅ 1.55, 0.50; recreation and stress management: x̅ 1.84, 0.36; prevention of complications: x̅ 1.84, 0.36) were at high level. During the same period only the mean score of exercise that fell into the moderate level. During the Ramadan period, the total mean score of health behaviours (x̅ 1.40, 0.49) together with those diet management (x̅ 1.11, 0.58), exercise (x̅ 1.16, 0.68), and prevention of complications (x̅ 1.14, 0.58) were rated in moderate level. However, during the Ramadan, the mean scores of the drug management, and recreation and stress management remained at high level (x̅ 1.80, 0.43, and x̅ 1.66, 0.49 respectively). In addition, the study results showed that the percentage of the study samples with blood sugar levels higher than 140 mg/dl during the Ramadan was lower than those recorded during the normal period (38.6%, and 52.1% respectively). And the percentages of the study samples with blood sugar levels ranged between 120 mg/dl and lower (28.1%), and 121-140 mg/dl (33.3%) during the Ramadan were higher than those recorded during normal period (22.9%, and 25.0% respectively). Hence, during Ramadan period, health professionals are recommended to give advices to Muslims with diabetes mellitus about the health practice, especially on diet management and self-care management in the event of hypoglycemia, to keep the adverse health condition under control.